Assessment of the current state of the telecommunications industry of the Republic of Kazakhstan - Daribekov, S.S.; Akbayev, E.T.; Mukashev, T.A.; Yerzhanova , S.K. (BUKETOV BUSINESS REVIEW, 2018)
This article is devoted to the current state of development of the telecommunications industry in the country. With the help of telecommunications, the processes of globalization are intensifying by increasing the volume of information provided through the information and telecommunications infrastructure. The market dictates to telecom companies the tasks of constantly increasing their competitiveness level based on the modernization and optimization of business processes and the introduction of advanced scientific and technical developments in the activities of companies. A peculiarity of the communication industry is the absence of a final product in material form. In the industry, the processes of conversion of electrical signals are carried out for economical, reliable and high-quality transmission of information to the specific recipient for which it is intended. The state of development of the telecommunications industry in Kazakhstan, in this article, was determined by an analysis of the following indicators: the dynamics of the physical volumes of services provided, the dynamics of the main indicators of the country's telecommunications industry, and the general structure of its revenues. At the same time, the relevant conclusions were drawn. This industry is fastgrowing, as it is provided by the technological process in the world. Information and telecommunication technologies play an extremely important role in the transformation of the economy, and in enhancing its competitiveness. In addition, a small share of the industry in the country's GDP speaks of its great investment potential. This potential is realized due to Kazakhstan joining the WTO and integrating the telecommunications sector into the global information infrastructure.